2005
DOI: 10.1002/path.1892
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase activity correlates with lymphangiogenesis and vascular endothelial growth factor‐C expression in head and neck squamous cell carcinoma

Abstract: Nitric oxide (NO) is a diatomic free radical molecule that has been implicated in tumour angiogenesis and progression of head and neck squamous cell carcinoma (HNSCC). However, the mechanism underlying the effect of NO on tumour spread remains largely unknown. Tumour lymphangiogenesis has recently received considerable attention and there is increasing evidence that it is relevant for metastasis to lymph nodes in HNSCC. Here, we study the correlation between inducible NOS synthase (iNOS) activity and lymphangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…NO regulates the vasomotor activity of lymphatic microvessels, 8,28 inducing dilation, and it may act as a lymphangiogenetic factor through interaction with VEGF-C, as previously demonstrated in breast cancer and head and neck squamous cell carcinomas. 5,29 Interestingly, VEGF-C-overexpressing melanomas showed enhanced tumor angiogenesis, suggesting a coordinated 30,31 CD105 is an endothelial marker that reacts uniquely with endothelial cells of newly formed vessels, and, specifically of immature tumor blood vessels. 32 Thus, microvessel density evaluated using a marker of activated endothelial cells, such as CD105, may depict the time-course of the neoangiogenetic process within the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO regulates the vasomotor activity of lymphatic microvessels, 8,28 inducing dilation, and it may act as a lymphangiogenetic factor through interaction with VEGF-C, as previously demonstrated in breast cancer and head and neck squamous cell carcinomas. 5,29 Interestingly, VEGF-C-overexpressing melanomas showed enhanced tumor angiogenesis, suggesting a coordinated 30,31 CD105 is an endothelial marker that reacts uniquely with endothelial cells of newly formed vessels, and, specifically of immature tumor blood vessels. 32 Thus, microvessel density evaluated using a marker of activated endothelial cells, such as CD105, may depict the time-course of the neoangiogenetic process within the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, more recent observations indicate that NO is involved in the regulation of lymphatic vessels permeability and flow 8 and we have recently demonstrated that iNOS activity correlated with lymphangiogenesis and spread to lymph nodes in head and neck squamous cell carcinoma. 5 It is possible that in the tumor microenvironment NO stimulates angiogenesis and/or lymphangiogenesis cooperatively with other proangiogenic and lymphangiogenic growth factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Human intratumoral lymphatic vessels consist of only 2 or 3 LVECs, which are small, irregular and collapsed. Consequently, these vessels are thought to provide no activities, although some of them show positive staining for proliferating cell nuclear antigens (9). A possible explanation for this finding is the rapid proliferation and tumor tissue division in human cancer cells, which increases the interstitial hydrostatic pressure and blocks the lumen of new lymphatic vessels (10).…”
Section: Morphology Of Tumor Lymphatic Vessels and Their Correlation mentioning
confidence: 99%
“…For example, VEGF-C expression correlates with COX-2 expression in breast cancer (Zhang et al 2008), and VEGF-C expression is stimulated by the inflammatory mediators interleukin-1b, TNF-a, and COX-2 and its induced prostaglandins (Ristimaki et al 1998;Su et al 2004). In head and neck cancer, the activity of inducible nitric oxide synthase (iNOS) is found to correlate with VEGF-C expression, lymphangiogenesis, and lymph node metastasis, and the human epidermoid carcinoma cell line A431 up-regulates VEGF-C on nitric oxide (NO) treatment (Franchi et al 2006). iNOS can be produced by tumor or stromal cells, including macrophages, and is induced by inflammatory cytokines or LPS.…”
Section: Leukocytes Tumor Lymphangiogenesis and Lymph Node Metastasismentioning
confidence: 99%